The Ethical Challenge of “Healthy Patients” [el “Paciente Sano”: Desafíos Éticos de la Medicina Preventiva] - Aurenque-Stephan, D (Sociedad Medica de Santiago, 2017)
This paper deals with the phenomenon of the “healthy patient”, an ethical issue receiving increased attention at a global level. The genesis of this phenomenon rests in the contradiction between a higher availability of technical and scientific resources for prevention and, paradoxically, the tendency towards an accelerated classification of healthy people as being at risk of developing disease. This manuscript focus on the ethical implications of the “healthy patient”, using a theoretical and philosophical approach. Therefore, this research aims to set forth the phenomenon of the “healthy patient” and its fundamental ethical problem, interpreting it as a contradiction between the perennial goal of medicine to maintain and promote health and the increasing use of technology. Thus, it can be hypothesized that the early classification of individuals as subjects at risk is a problem of time. Finally an interpretation from a philosophical point of view will be presented to offer a better understanding of the ethical problem of the “healthy patient” and to elucidate possible strategies of action for physicians and their patients. © 2017, Sociedad Medica de Santiago. All rights reserved.